TECTONIC SETTING OF SYNOROGENIC GOLD DEPOSITS OF THE PACIFIC RIM - Goldfarb R.J.; Phillips G.N.; Nokleberg W.J. (My University, 1998)
More than 420 million oz of gold were concentrated in circum-Pacific synorogenic quartz lodes mainly during two periods of continental growth, one along the Gondwanan margin in the Palaeozoic and the other in the northern Pacific basin between 170 and 50 Ma. These ores have many features in common and can be grouped into a single type of lode gold deposit widespread throughout clastic sedimentary-rock dominant terranes. The auriferous veins contain only a few percent sulphide minerals, have gold:silver ratios typically greater than 1:1, show a distinct association with medium grade metamorphic rocks, and may be associated with large-scale fault zones. Ore fluids are consistently of low salinity and are CO2-rich.
Keywords: Palaeozoic; Paleozoic; Палеозой